Qualitative Inquiry in an Age of Educationalese - Fischman, Gustavo Enrique; Tefera, Adai (Education Policy Analysis Archives, 2014)
In this introduction we reflect on two key questions that initiated this special issue on qualitative inquiry: What can qualitative researchers do to regain their post-paradigm-wars cache? How do we avoid distracting “science wars” in the future? We suggest that the strong tendency to narrow the research methods accepted as “scientific” – because they adopt quantitative perspectives and are presumed a priori to be more rigorous – has created an educationalese, a narrative of rigid categories that has not necessarily contributed to more effective or persuasive educational research. The article ends by suggesting that the use of “knowledge mobilization” strategies would help to strengthen qualitative research and educational research in general.